A NEW WIDE-FIELD TELESCOPE WITH A MIRROR DIAMETER OF 600 MM FOR THE TELESCOPE NETWORK OF THE ODESSA OBSERVATORY - Fashchevsky, N. N.; Podlesnyak, S. V.; Bondarenko, Yu. N.; Andrievsky, S. M.; Romanyuk, Ya. O. (Одеські астрономічні публікації, 2020)
Optical scheme of the new wide-field telescope of the telescope network of Odessa Obser- vatory is described.The telescope optical layout is designed as a mirror-lens system with a Ross-type two-lens corrector and a hyperbolic primary mirror with diameter of 600 mm. The prime focus corrector is capable of imaging a field of 2 degrees, the root- mean-square radius of the diffraction spot is about 4.5 µm, which is 2.5 times larger than that of the diffraction-limited spot (Airy disk).